Influence of lactose fermentative yeast on fermented serum and malt drink parameters - Chepel, Natalia; Grek, Olena; Krasulya, Olena (My University, 2013)
Influence of different lactose fermentative yeast races (Zygosaccharomyces lactis 868-K, Saccharomyces lactis 95, Kluyveromyces lactis 469) on physical and chemical parameters of fermented wort in comparison with the standard ones was investigated. The results prove the highest fermentative activity of Zygosaccharomyces lactis 868-K yeast, in particular: ethyl alcohol content – 1.0 v. %, sodium hydroxide solution acidity with concentration of 1 mol/dm3 per 100 cm3 of drink – 3,5 cm3, drink stability at 20 C – 5 days. Physical and chemical parameters of wort fermented with Saccharomyces lactis 95 and Kluyveromyces lactis 469 yeast are considerable lower than the standard ones which points at rather low activity of ferments catalyzing lactose hydrolysis.
Keywords: fermentation waste products; побічні продукти бродіння; побочные продукты брожения; serum and malt drink; сироватко-солодовий напій; сывороточно-солодовый напиток; кафедра технології молока і молочних продуктів